Comparative assessment of economic development in the countries of the European Union - Trishch, Roman Mikhailovich; Sichinava, Alexander; Bartoš, Vojtěch; Stasiukynas, Andrius; Schieg, Martin (Journal of Business Economics and Management, 2023)
Investment, the entry of foreign firms depends of a large extent on the country’s goodwill, which is reflected in various ratings. This representation of the situation is approximate, as it does not estimate the differences between the values of the indicators with adjacent grades. This can be avoided by dividing countries into homogeneous groups. It is appropriate to do so on the basis of non-linear grouping rather than linear grouping. It is based on the transformation of data into a dimensionless scale and linear grouping. In the case, its homogeneity increases thanks to the levelling of the most distinctive values and the alignment of the statistical characteristics of the groups. The aim of the article is to propose in principle, a new approach to the ranking of countries on the basis of their level of economic development. It was found that the nonlinear decision of countries into homogenous groups and compared to the linear grouping more accurately reflect the current situation.